RELIGION ON THE INTERNET - Cowan, Douglas (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
It has become something of a truism to note that few religions that exist offline have not found some kind of presence on the World Wide Web. Ranging from very elaborate, technologically sophisticated sites such as the www.scientology.org (Church of Scientology) or www.lds.org (Church of Jesus Christ of Latter-day Saints) to simple congregational Web pages that list little more than the church address, telephone number, and meeting times, from Web sites promoting the fundamentalist agendas of the evangelical Christian countercult (www.carm.org) to those advocating particularly violent forms of Hindu nationalism (www.hinduunity.org), and from online Bibles to Wiccan Books of Shadows, the World Wide Web reflects online the vast spectrum of religion in the offline world. As well, the Internet has become an important tool in researching a wide variety of religious topics.